2022
DOI: 10.1007/s40120-022-00409-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diffusion–Perfusion Mismatch in Acute Ischemic Stroke with a New Automated Perfusion-Weighted Imaging Software: A Retrospective Study

Abstract: Introduction The aim of this study was to evaluate the accuracy of automated software (iStroke) on magnetic resonance (MR) apparent diffusion coefficient (ADC) and perfusion-weighted imaging (PWI) against ground truth in assessing infarct core, and compare the hypoperfusion volume and mismatch volume on iStroke with those on Food and Drug Administration-approved software (RAPID) in patients with acute ischemic stroke. Methods We used the single-volume decomposition meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…ZL202110266924.6 and ZL202110226735.6) has been described elsewhere. 22 Patients will be excluded if CT scan indicating intracranial haemorrhagic diseases, being given any IVTs other than alteplase before EVT, being allergic to any components of edaravone dexborneol injection, having a history of congenital or acquired haemorrhagic disease, with an elevated systolic blood pressure surpassing 180 mm Hg or diastolic blood pressure exceeding 110 mm Hg after therapy, being in cases where the serum levels of alanine aminotransferase or aspartate transaminase are found to exceed three times the upper limit of normal, or if the current serum creatinine exceeds 1.5 times the upper limit of normal, or if the estimated glomerular Open access filtration rate falls below 60 mL/min, etc (figure 2). Patients who have recently been administered or are currently receiving any Chinese traditional medicine containing borneol should also be excluded.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…ZL202110266924.6 and ZL202110226735.6) has been described elsewhere. 22 Patients will be excluded if CT scan indicating intracranial haemorrhagic diseases, being given any IVTs other than alteplase before EVT, being allergic to any components of edaravone dexborneol injection, having a history of congenital or acquired haemorrhagic disease, with an elevated systolic blood pressure surpassing 180 mm Hg or diastolic blood pressure exceeding 110 mm Hg after therapy, being in cases where the serum levels of alanine aminotransferase or aspartate transaminase are found to exceed three times the upper limit of normal, or if the current serum creatinine exceeds 1.5 times the upper limit of normal, or if the estimated glomerular Open access filtration rate falls below 60 mL/min, etc (figure 2). Patients who have recently been administered or are currently receiving any Chinese traditional medicine containing borneol should also be excluded.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…In a previous study, we demonstrated that the automated software iStroke (Beijing Tiantan Hospital and Biomind, Beijing, China) predicted perfusion parameters on magnetic resonance perfusion-weighted imaging. 15 However, whether iStroke has similar accuracy by measuring perfusion volumes on CTP using deep neural networks to the RAPID software and its predictive ability for clinical functional outcomes are unclear. Therefore, we sought to compare the agreement of iStroke and RAPID on CTP imaging with ground truth on DWI and the association of infarct core volume (ICV) by softwares with clinical functional outcomes in patients with AIS who underwent endovascular treatment (EVT) with complete recanalisation.…”
Section: Open Accessmentioning
confidence: 99%